Effect of Maternal Anaemia on APGAR Score of Newborn - Muhammad Owais Ahmad,Umay Kalsoom (Journal of Rawalpindi Medical College, 2015)
Background: To study the effect of maternal anaemia on APGAR score of newborn and to compare it with that of non-anaemic mothers. Methods: In this cross sectional study 100 subjects were divided into two groups; each containing 50 subjects on the basis of consecutive non probability sampling . Group A included 50 anaemic pregnant women (haemoglobin < 11.0 g/dl) and group B 50 non-anaemic(haemoglobin >11.0 g/dl) pregnant women. In APGAR scoring five factors (which Apgar stands for) were used to calculate the baby’s condition and each scored on a scale of 0 to 2, with 2 being the best score.A baby who scored 8 or above was considered in good health and a score of less than 8 was considered low. Data was compared using t-test at a confidence level of 95%. Frequencies were calculated for categorical data. These were compared using chi-square test, and p<0.05 was statistically significant. Results: Difference between the two groups was found to be statistically very significant (p<0.003)in this variable also, as 16 out of 50 babies delivered to mothers in the anemic group showed a low APGAR at one minute as against 04 out of 50 in the babies delivered to the mothers in the non anemic group .Difference between the two groups was found to be statistically significant (p<0.012) . Twelve out of 50 babies delivered to mothers in the anemic group in our study showed a low APGAR at five minutes as against 03 out of 50 in the babies delivered to the mothers in the non anemic group.The number of anemic mothers who showed a low APGAR score of their infants were more at both one (32%) and five minutes (24%) as compared to the non anemic group (08% and 06% respectively), with a statistically highly significant difference of these two variables (p<0.003 and p<0.01 respectively) between the two groups. Conclusion: There was a linear relationship of maternal anaemia in pregnancy with greater probability of low APGAR score at one and five minutes.